PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP MINAT BELI ULANG DI PARAKOPI CAFÉ BATUSANGKAR - Hemalia Putri; Lise Asnur (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
AbstractResearchers found issues related to repurchase intention concerning service quality and location at Café Parakopi Batusangkar, which led to the undertaking of this study. This study's goal is to describe the level of service quality., location, and repurchase intention, as well as to analyze the influence of service quality and location on repurchase intention at Parakopi café Batusangkar. This study utilized a quantitative approach with an associative-causal design. The research sample consisted of 93 respondents, selected through purposive sampling. Data collection was conducted using questionnaires distributed to customers visiting Parakopi Café. The instrument was tested for validity and reliability.The analysis prerequisites were checked for normality, multicollinearity, and heteroscedasticity. The hypothesis testing was performed using multiple linear regression and coefficient of determination. The results indicated that the average respondent's perception of service quality was 78.86%, categorized as good. The average respondent's perception of the location was 78.06%, also categorized as good. Furthermore, the average respondent's repurchase intention was 67.73%, categorized as moderate. The multiple linear regression test resulted in an A significance level of 0.000 < 0.05 with an F-value of 16.221, indicating that the regression model is valid. This means that service quality and location significantly influence repurchase intention. The R Square value of 0.309 indicates that 30.9% of the repurchase intention at Parakopi café is influenced by service quality and location, while the remaining 69.1% is influenced by other variables not discussed in this study.